Анализ статистических характеристик радиоканалов систем WI-MAX - Коляденко, Ю. Ю.; Бойко, Е. В.; Хафиз Мухаммад И. (ХНУРЭ, 2011)
Abstract. Statistical characteristics of WI-MAX system radio channels using MIMO technologies with two proper subchannels under uncorrelated Rayleigh fading signal conditions were analyzed. The dependence of probability-density function of the channel array proper numbers was obtained and that determines the probability of bit errors in WI-MAX systems.
Keywords: телекоммуникационные сети; развертывание сетей